Legal Protection for Child Victims of Cyberbullying: Policy Analysis, Implementation and Challenges in The Digital Era - Safa Cyrilla Apsarini; Labib Muttaqin (Universitas Muhammadiyah Surakarta, 2025)
The rapid development of information technology has driven globalization and brought the world into the modern era, presenting various opportunities alongside negative impacts on social life. One of the concerning negative effects is cyberbullying, which can significantly influence children's psychological well-being and social interactions. This study employs a normative legal method by analysing relevant laws and regulations. Data analysis was conducted qualitatively through logical reasoning, induction, deduction, analogy, and comparison. Legal protection for victims of cyberbullying in Indonesia is enshrined in several laws and regulations, such as Law Number 35 of 2014 and Law Number 1 of 2024. However, the implementation of these policies encounters various challenges, including a lack of public awareness and inadequate facilities and infrastructure for victims. There is a need for enhanced socialization, education, and evaluations of the effectiveness of existing policies. Legal protection for child victims of cyberbullying has been established in law, but its implementation requires strengthening through oversight, education, and collaboration among the government, educational institutions, and the community.